THE ROLE OF DIGITAL TECHNOLOGIES AND DISTANCE LEARNING METHODS IN IMPROVING THE SYSTEM OF ADVANCED TRAINING FOR MID-LEVEL MEDICAL AND PHARMACEUTICAL WORKERS IN UZBEKISTAN - Rasulova D.S; Urazaliyeva I.R (Modern American Journals, 2025)
This article is dedicated to studying the role of digital technologies and distance learning methods in improving the system of continuous professional education and advanced training for mid-level medical (nurses, feldshers, laboratory specialists) and pharmaceutical workers in the Republic of Uzbekistan. The relevance of the topic is related to the digital transformation of Uzbekistan's healthcare system, in particular the “Digital Uzbekistan-2030” strategy and the needs arising from the impact of the COVID-19 pandemic. The article analyzes national and international experiences, including digital education models in the USA, Germany, and European Union countries, as well as the results of empirical research conducted in medical institutions in the Tashkent, Samarkand, Bukhara, and Fergana regions of Uzbekistan. The research methodology is based on surveys, statistical analysis, experimental distance courses, and qualitative interviews. The results show that the introduction of digital methods increases the efficiency of advanced training and reduces costs. The discussion provides detailed coverage of problems and suggestions. The article provides practical recommendations for the Ministry of Health and educational institutions. This work emphasizes the importance of healthcare system and contributes to alignment with global standards. The research results were conducted in 2023-2025, and its relevance is related to Uzbekistan's aspiration for universal healthcare coverage and the development of digital technologies. digitalization in reforming Uzbekistan's
Keywords: mid-level medical workers, nurses' qualifications, pharmaceutical personnel, continuous professional education, advanced training system, digital technologies, distance learning, electronic platforms, digital transformation, “Digital Uzbekistan-2030”, healthcare reforms, COVID-19.